KEMAMPUAN BERBICARA SISWA LAKI – LAKI DAN PEREMPUAN SMAN 2 BANGKINANG DALAM MENDESKRIPSIKAN GAMBAR - Triani Oktarina Oktarina; Hadriana '; Erni, S.Pd, M.Hum ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was the speaking ability of male and female students of SMAN 2 Bangkinang in describing pictures.The aim of this research was to know the differences between speaking ability of male and female students of SMAN 2 Bangkinang in describing pictures.The population of this research is the second grade of SMAN 2 Bangkinang. The data were collected by administring the speaking test to 23 male students and 23 female students who were selected by using proportional random sampling method. In conducting this research, there were 4 different pictures which used to know the students’ speaking ability in describing pictures based on five aspects: pronunciation, grammar, vocabulary, fluency, and comprehension. To get the quantitative data in this research, the three raters were involved to give the scores of students’ speaking ability. From the result of the speaking test in five aspects of speaking ability, the writer concluded that there are differences between speaking ability of male and female students of SMAN 2 Bangkinang in describing pictures. However, the difference between male students and female students is significant. It is convinced by the statistical result of the hypothesis test. The test by means of t-test formula shown that t calculated = 5,18 > ttable = 2,015 at 95% level of significance by 44 degrees of freedom